Cervantes and Lorca as a legacy and challenge in the field of humanities within the latin american context (Contextos: Estudios de Humanidades y Ciencias Sociales, 2017)
2016 was a year of fundamental celebrations in the historical and literary record of humanity: we celebrated two of the greatest writers in Spanish or Castilian language: the 400th anniversary of the death of Miguel de Cervantes (+ April 22, 1616) and the 80th anniversary of the murder of Federico García Lorca (+18 August 1936). It has been a period to think through how their work and their lives, which took place in such distant times, still mark a process of evolution in the poetics that is produced in Latin America, and also serve as an intellectual motivation and echo in the contemporary thought. Having diverse biographies and being different literary geniuses, Cervantes and Lorca keep in force as intertextual, transtextual and hypertextual essence.